Nitrogen-to-Protein Conversion Factors for Edible Insects on the Swiss Market: T. molitor, A. domesticus, and L. migratoria - Boulos, Samy; Tännler, Anina; Nyström, Laura (Frontiers in Nutrition, 2020)
With an increasing worldwide demand for animal protein, insects are becoming a promising sustainable option for meat protein replacement. However, reported protein contents of insects are often overestimated when calculated as “crude protein” = 6.25×nitrogen content (N), compared to true protein contents quantified from the sum of amino acid (AA) residues. In this study, the main two types of usual nitrogen-to-protein conversion factors kp and kA were determined on the basis of true protein/total nitrogen and true protein/protein nitrogen, respectively, with focus on the three insect species legally sold on the Swiss food market. T. molitor (mealworm larvae), A. domesticus (house crickets), and L. migratoria (locusts) from various breeders were analyzed for total and amide nitrogen, chitin, and AA composition. Careful control experiments of insect samples spiked with a protein standard were conducted to establish the recovery of true protein, which was with >95% excellent. Mealworms, crickets, and locusts exhibited similar AA-profiles and true protein contents of 51, 55, and 47 g/100 g (dry weight basis), respectively. Specific conversion factors kp showed little variability between the three insect species with 5.41, 5.25, and 5.33 for mealworms, crickets, and locusts, respectively, and confirmed an average ~17% overestimation of protein contents when using 6.25×N. The determined average kp of 5.33 is supported by extracted literature data and is suggested for general use instead of 6.25×N to calculate more accurate insect protein contents, whereas the average pure protein conversion factor kA of 5.6 is proposed for use in the case of insect protein isolates.